2000
DOI: 10.1097/00007890-200006150-00032
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Human Betaherpesviruses After Renal Transplantation

Abstract: HHV-7 should be further investigated as a possible co-factor in the development of CMV disease in renal transplant patients and may potentially exacerbate graft rejection. No clear pathological role was observed for HHV-6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…These results were similar to previous reports focusing on hematopoietic stem cell or solid organ transplant patients [22,2831]. Chan et al [28] investigated bone marrow transplant recipients, and reported CMV in 61%, HHV-6 in 28% and HHV-7 in 53% of the individuals, while Kidd et al [29] researched renal transplant patients and observed parallel viruses in 58%, 23% and 46% of the patients. A high percentage of infected patients were also recorded by Wang et al [30], and this is in agreement with the observations presented here, especially with respect to CMV and EBV incidence.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results were similar to previous reports focusing on hematopoietic stem cell or solid organ transplant patients [22,2831]. Chan et al [28] investigated bone marrow transplant recipients, and reported CMV in 61%, HHV-6 in 28% and HHV-7 in 53% of the individuals, while Kidd et al [29] researched renal transplant patients and observed parallel viruses in 58%, 23% and 46% of the patients. A high percentage of infected patients were also recorded by Wang et al [30], and this is in agreement with the observations presented here, especially with respect to CMV and EBV incidence.…”
Section: Discussionsupporting
confidence: 90%
“…Otherwise, it is well-known that CMV alone or in concomitant presence of other herpesviruses may initiate or exacerbate GvH disease [39], hence it is difficult to pinpoint the cause of such high aminotransferases level in our patients. The possible contribution of HHV-7 to the process of transplant rejection has already been indicated by other authors [29]. On the other hand, Chan et al [40] did not observe, in pediatric allogeneic recipients of HSCT, a significantly higher risk for development of acute GvHD in HHV-7-positive patients.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…These include CNS disease [53], myelosuppression [54], aGVHD [55], and allograft dysfunction and rejection [56]. Data from a number of studies suggest a potential indirect effect of HHV-7 to increase rates of CMV reactivation and disease in HCT [57] and SOT [58,59] recipients, but this is not a consistent finding [52]. Future studies of HHV-6B should incorporate testing for HHV-7 to advance our understanding of its possible significance in transplantation.…”
Section: Human Herpesvirusmentioning
confidence: 99%
“…Patients with CMV disease were more likely to have HHV-7 DNA detection than those with asymptomatic CMV infection (31% vs 0%, P = 0.13) [38]. In a study in renal transplant recipients, patients with CMV and HHV-7 coinfection were more likely to have CMV disease compared with those with CMV infection only [39]. In liver transplant recipients, however, no pathogenic effect of HHV-7 was documented [40].…”
Section: Human Herpesvirus-7mentioning
confidence: 95%